(untitled) (Research, Society and Development, 2022)
The research evaluated the growth, development and productivity of watermelon (Citrullus lanatus), variety Crimson Sweet and the contribution of nutrients to the soil from the use of irrigation with fish farming wastewater (AR) and supply water (AA) with and without organic fertilization. The experiment was conducted in the community of Vila Jessé at Km 35, Bragança/Pará. A completely randomized design was adopted with treatments arranged in a 2 x 2 factorial scheme, with 2 types of irrigation water (AR) and (AA) and 2 fertilization levels (with and without organic fertilization) and 10 replications, totaling 40 plots. Each plot consisted of an average of 4 plants. At 35 days after transplanting (DAT), the average number and length of branches were evaluated; and, at 64 DAT, the average fruit volume, productivity and, at the end of production, the average fruit weight and the contribution of nutrients in the soil. Regardless of the type of water used (A.R. or A.A.) treatments with organic fertilization showed the best averages. Just as with the use of A.R, better productivity was achieved, for the average number of branches, the A.A. presented the highest average. The use of A.R. promoted significant improvements in soil nutrition. The use of A.R. through drip irrigation proved to be a viable alternative for watermelon production in dry periods, improving soil nutrition and enabling the commercialization of this fruit in off-season periods.